2012
DOI: 10.3892/mco.2012.1
|View full text |Cite
|
Sign up to set email alerts
|

Nestin regulates epithelial-mesenchymal transition marker expression in pancreatic ductal adenocarcinoma cell lines

Abstract: Abstract. Nestin, a class VI intermediate filament, is a neuronal stem/progenitor cell marker that is also expressed by various types of cancer, including pancreatic ductal adenocarcinoma (PDAC). We previously detected nestin expression in approximately 30% of PDAC cases, and found that nestin promotes the migration, invasion and metastasis of cells. Findings of recent studies have shown that epithelial mesenchymal transition (EMT) is important in the invasion and migration of cancer. In the present study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Nestin regulates stemness, cell growth, and invasion in glioblastoma cells through the alteration of HSC71 . However, the effect of nestin on pancreatic cancer cell proliferation remains controversial . We previously found that inhibiting nestin expression by short hairpin RNA (shRNA) suppressed growth of the glioblastoma cell line A172, the melanoma cell line A375, and the lung cancer cell line H1975 .…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Nestin regulates stemness, cell growth, and invasion in glioblastoma cells through the alteration of HSC71 . However, the effect of nestin on pancreatic cancer cell proliferation remains controversial . We previously found that inhibiting nestin expression by short hairpin RNA (shRNA) suppressed growth of the glioblastoma cell line A172, the melanoma cell line A375, and the lung cancer cell line H1975 .…”
Section: Discussionsupporting
confidence: 45%
“…Nestin phosphorylation affects several pancreatic cancer cell behaviors including cell growth, migration, invasion, and metastasis. Data from the present study and our previous studies indicate that nestin is a key factor in pancreatic cancer invasion and metastasis, and inhibition of nestin expression or phosphorylation may be a novel therapeutic strategy for treating pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the lungs of hypobaric hypoxic rats, numerous epithelial cells apparently underwent type II EMT depicted by the co‐expression of E‐cadherin and collagen type I (Kage & Borok, ; Yang et al, ; Pain et al, ). In type III EMT, nestin expression was identified as a novel phenotype required for proliferation and metastasis and a similar paradigm may be prevalent during Type II EMT (Ishiwata et al, ; Hagio et al, ; Matsuda et al, ). The removal of FBS led to the acquisition a mesenchymal phenotype by a subpopulation of primary passage adult rat alveolar epithelial cells depicted by the downregulation of E‐cadherin and concomitant induction of collagen type I.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that nestin expression in renal‐ and lung‐derived resident stromal cells was upregulated following exposure to TGF‐β (Sakairi et al, ; Chabot et al, ). Nestin was also induced during Type III EMT and implicated in the acquisition of a proliferative and metastatic phenotype (Ishiwata et al, ; Hagio et al, ; Matsuda et al, ). Thus, it is tempting to speculate that one or more of the identified paradigms implicated in the appearance of pulmonary fibroblasts may be characterized by nestin expression.…”
mentioning
confidence: 99%